Similarity of ecological niche of Pinus montezumae and P. pseudostrobus (Pinaceae) in Mexico: implications for the selection of seed production and conservation areas - Manzanilla Quiñones, Ulises; Delgado Valerio, Patricia; Hernández Ramos, Jonathan; Molina Sánchez, Agustín; García Magaña, J. Jesús; Rocha Granados, Ma. del Carmen (Instituto de Ecología, A.C., 2018)
Background and Aims: Ecological niche models have been used to understand how species can change or persist in an environmental and geographical space over time. The aims of the study were i) to model the ecological niche of Pinus montezumae and Pinus pseudostrobus in Mexico, ii) to evaluate and compare the similarity and equivalence of niche suitability between the distribution areas of both species, and iii) to propose potential geographic zones for the delimitation of seed-producing and conservation areas for each species.Methods: We used geographical data on distribution of species and climatic, topographic, elevation and soil data as environmental predictors, which were modeled based on the Maximum Entropy algorithm. The parameters of similarity (I) and equivalence (D) were estimated to know the degree of overlap of the niche of the species. For the selection of seed areas, environmental data were used that defined the distribution of each species and dasometrics of the National Forest and Soil Inventory (INFyS).Key results: The models show that the two species have similar areas of high suitability, distributed in the Trans-Mexican Volcanic Belt and the Sierra Madre del Sur. The highest contribution to the models for Pinus pseudostrobus were the variables average annual temperature (41.3%) and total annual rainfall (14.3%), whereas the soil (31.1%) and altitude (29%) were determinants in P. montezumae. The niche overlap analysis indicates that the observed value of equivalence (D=0.430) is less than the similarity value (I=0.610), suggesting that the species have a similar niche but that this is not equivalent, which could be in the process of diversification.Conclusions: The suitability of the ecological niche is similar for the two pine species, but it is not equivalent as they present differential environmental variables. These results have implications for the selection of potential areas for seed production and conservation of each species.